Design and development of a web-based seminar and workshop management application at STMIK Jayakarta - Pambudi, Grandis Dias; Budiman, Thomas; Sianipar, Anton Zulkarnain (Jurnal Mandiri IT, 2025)
The rapid development of information technology offers opportunities to improve the efficiency and quality of academic event management, including seminars and workshops. This study aims to design and develop a web-based application that facilitates the digital management of seminars and workshops at STMIK Jayakarta. The application includes key features such as online attendance recording using a unique event code, real-time interactive Q&A submission, and automatic certificate generation for both participants and speakers. The system adopts a two-role model—admin and non-admin—where non-admin users may act as participants, moderators, or speakers depending on the event, allowing for flexible role assignments. Developed using HTML, PHP, JavaScript, and MySQL, the application improves data accuracy, reduces the risk of data loss, and simplifies administrative processes. This system is expected to serve as a foundation for future development of similar academic applications.